The role of educator in food and nutrition by health professionals in the context of Family Health Care - Werbicky CARVALHO-GEBRAN, Fernanda; Rosendo VINCHA, Kellem Regina; CERVATO-MANCUSO, Ana Maria (Revista de Nutrição, 2023)
Objective This study aimed to understand the role of health professionals in educational groups that have food and nutrition as their theme. Methods Qualitative research was conducted in the city of São Paulo, with professionals from the Family Health Strategy. Interviews were conducted to understand the professionals’ perceptions of the roles played in groups. These were analyzed using the Discourse of the Collective Subject technique. The groups’ observations on the performance of the professionals in their mediations were analyzed, based on the following items: meeting organization, communication, support, participation, confirmation of messages, and encouragement to ask questions. Results Twenty-two professionals from different backgrounds were interviewed, and 23 groups of different configurations were observed. The speeches showed that the professionals recognize themselves as organizers, mediators, and evaluators of the groups. Under the topic of organization, teamwork was highlighted. In mediation, there was an assumption of different types of performance that are inserted in conceptions of banking education and dialogical education. In the theme of evaluation, conflict and contradiction arose, pointing out the complexity of approaching a group theme when professionals seek a more horizontal posture with users. Observation of the groups revealed a duality between discourse and professional practice, which is surrounded by contradictions inserted into academic formation and the work process of the teams. Conclusion It was possible to understand the complexity of the practice of professionals when approaching the theme in groups, evidencing the need for spaces of care and for permanent education, especially when regarding professionals who use problematic and active approaches.